Evaluation of crestal bone levels using simvastatin as an adjuvant around immediate implants - A clinico radiographic study - Hymasre Betha; M Rajmohan; Radhika Thakkar; Bezgam R Surya; Manoj Shetty; Puja Sankla; Rahul Tiwari (Wolters Kluwer Medknow Publications, 2024)
Objective: Simvastatin was used as an adjuvant medication in this clinico-radiographic investigation to assess the impact on crestal bone levels around immediate implantation. Materials and Methods: A randomized controlled trial with 50 patients who needed an implant placed right away was done. Simvastatin was used as an adjuvant in groups ((Group A), whereas group (Group B)) served as the control group for the participants. At baseline and during follow-up visits, clinical measures such as probing depth (PD) and bleeding on probing (BOP) were measured. At baseline and 12 weeks, radiographic measurements of crestal bone levels were taken. Results: At 12 weeks, Group A demonstrated a significantly lower PD and BOP than did Group B. Furthermore, at 12 weeks, Group A showed greater crestal bone preservation than did Group B. The results of the statistical analysis showed that the two groups were significantly different. Conclusion: The results of this study indicate that simvastatin use as an adjuvant medication after immediate implant insertion contributes to better clinical outcomes and greater crestal bone preservation. Simvastatin may be helpful in increasing bone regeneration, decreasing inflammation, and soft tissue healing. These findings demonstrate how simvastatin may be used as an additional therapy to enhance the effectiveness of rapid implant implantation operations.